2011
DOI: 10.1152/physiol.00049.2010
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Paradox: Differential Regulation of Ion Transport in Distal Nephron

Abstract: The mechanisms through which aldosterone promotes apparently opposite effects like salt reabsorption and K ϩ secretion remain poorly understood. The identification, localization, and physiological analysis of ion transport systems in distal nephron have revealed an intricate network of interactions between several players, revealing the complex mechanism behind the aldosterone paradox. We review the mechanisms involved in differential regulation of ion transport that allow the fine tuning of salt and K ϩ balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 97 publications
2
113
0
2
Order By: Relevance
“…In line with this, recent studies have shown that angiotensin II directly inhibits ROMK, further contributing to potassium conservation during hypovolemia [49,129,140]. The effects of angiotensin II on NCC and ROMK therefore help to understand the aldosterone paradox, the question how aldosterone increases sodium reabsorption during hypovolemia, but potassium secretion during hyperkalemia [3,122]. Further insight into the aldosterone paradox comes from the effects of potassium on NCC.…”
Section: Structure-function Relationshipmentioning
confidence: 85%
See 1 more Smart Citation
“…In line with this, recent studies have shown that angiotensin II directly inhibits ROMK, further contributing to potassium conservation during hypovolemia [49,129,140]. The effects of angiotensin II on NCC and ROMK therefore help to understand the aldosterone paradox, the question how aldosterone increases sodium reabsorption during hypovolemia, but potassium secretion during hyperkalemia [3,122]. Further insight into the aldosterone paradox comes from the effects of potassium on NCC.…”
Section: Structure-function Relationshipmentioning
confidence: 85%
“…It has been suggested that NCC is expressed in various other tissues but this has not been confirmed [29]. In the kidney, NCC is located in the early part of the DCT (also called DCT1) (Figure 1), but gradually decreases along the later part of the DCT (DCT2), where it co-localizes with the epithelial sodium channel (ENaC) [3].…”
Section: Typical Hallmarks Of Nccmentioning
confidence: 99%
“…1 After induction of ENaC deletion along the nephron, NCC is significantly less phosphorylated. This finding is unexpected, because the Scnn1a…”
Section: Aldosterone-independent Regulation Of Ncc In Scnn1amentioning
confidence: 99%
“…This mechanism is commonly referred as the aldosterone paradox, but how aldosterone exerts these apparently opposite effects is not yet completely understood. 1 Na + reabsorption in the distal nephron occurs through two different means: the electroneutral thiazide-sensitive Na + /Cl 2 cotransporter (NCC) expressed mainly in the DCT1, with lower expression in the DCT2, and the amiloridesensitive epithelial sodium channel (ENaC) expressed in the aldosterone-sensitive distal nephron (ASDN), namely the DCT2, CNT, and CD. Na + and K + are the most important cations for the transmembrane potential across the plasma membrane, and electrogenic Na + reabsorption through ENaC increases the driving force for K + transport and thus, K + excretion.…”
mentioning
confidence: 99%
“…Both NCC SV and NCC 3 are present as glycosylated oligomeric structures in uEVs [74,75]. Hence, uEVs were used to assessed the role of NCC SV in vivo .…”
Section: The Role Of Nccsv In (Patho)physiologymentioning
confidence: 99%